Chinese expert consensus on vaginal self-sampling with high-risk human papillomavirus testing for cervical cancer screening - Linhong Wang; Yun Zhao; Beihua Kong; Ding Ma; Ruifang Wu; Hui Du; Xinfeng Qu; Lihui Wei; Long Sui; Mingzhu Li; Fanghui Zhao; Jingran Li (Gynecology and Obstetrics Clinical Medicine)
Cervical cancer is one of the most common cancers in women globally and remains the leading cause of cancer-related death among women in low- and middle-income countries. It is more prevalent in populations that are unscreened or underscreened. Improving screening coverage presents a global challenge. Self-collected cervical cancer screening allows women to collect samples for high-risk human papillomavirus (HR-HPV) testing on PCR-based tests, effectively increasing screening rates for cervical cancer. In light of the push for HR-HPV testing as a primary cervical cancer screening strategy and considering the current status of cervical cancer screening in China, experts from five academic societies developed a consensus that including the definition, value, advantages, applicable people, screening proposal, tools and methods, process, sampler distribution form, organisational screening model, HPV DNA testing, abnormal results management of vaginal self-sampling, information system construction, management quality control and so on, aims to guide the standardised application of vaginal self-sampling screening, enhance cervical cancer screening coverage in China and advance the efforts to eliminate cervical cancer in the country.